Respuestas
Respuesta dada por:
3
f(x)=2x²-3x
f(-2)=2x²-3x
f(-2)=2(-2)²-3(-2)
f(-2)=2(4)+6
f(-2)=8+6
f(-2)=14
f(0)=2x²-3x
f(0)=2(0)²-3(0)
f(0)=2(0)-0
f(0)=0
f(a+1)=2x²-3x
f(a+1)=2(a+1)²-3(a+1)
f(a+1)=2(a²+2a+1)-3a-3
f(a+1)=2a²+4a+2-3a-3
f(a+1)=2a²+a-1
Saludos!!
f(-2)=2x²-3x
f(-2)=2(-2)²-3(-2)
f(-2)=2(4)+6
f(-2)=8+6
f(-2)=14
f(0)=2x²-3x
f(0)=2(0)²-3(0)
f(0)=2(0)-0
f(0)=0
f(a+1)=2x²-3x
f(a+1)=2(a+1)²-3(a+1)
f(a+1)=2(a²+2a+1)-3a-3
f(a+1)=2a²+4a+2-3a-3
f(a+1)=2a²+a-1
Saludos!!
yekaisa1314:
muchas gracias por tu ayuda
Preguntas similares
hace 6 años
hace 9 años
hace 9 años
hace 9 años